“Determinación de la eficiencia de telenomus podisi, parasitoide de posturas d epiezodorus guildinii en soya bajo condiciones de laboratorio en buenos aires, provincia de picota” - Calle Roalcaba, Orly Denisse (2006)
The present investigation work was carried out in the biologic control laboratory belong to San Fernando S.A. enterprise, in Buenos Aires district, Picota's province, with the following aims: Establish the raising of the parasitoid Telenomus podisi and its host Piezodorus guildinii; and determine the efficiency of of the parasitism under laboratory conditions for its possible great raising and liberation on soybean crops. The climate conditions shown during the period of fulfillment of this investigation work were: min. temperature = 19, 33 ºC, max temperature = 34, 96 ºC, relative humidity = 69, 73%, pluvial precipitation = 96, 24, this data were taken from the metereological station belong to San Fernando S.A. enterprise. We used 7 population densities of the parasitoid (0,1, 3,5,7,9 and 11 couples of T. podist) on 100 eggs of Piezodorus guildinii. We evaluated the most important biologic parameters of the host and its parasitoid. The period life of Piezodorus guildinii varies from 52,5 to 62,5 days for males and from 62,5 to 72,5 for females, pre copulate period of 11,5 days, 3 days until the oviposition , 2, 7 masses/female. The optimum density for the parasitism was 9 couples of T. podisi, this treatment had 100% of efficiency, the sex ratio of the parasitoid was of 1 :3 (males: female).